The role of financial governance in achieving net income before tax An applied study in the Kurdistan International Bank for Investment and Development, registered in the Iraq Securities Commission - Regular Market - Zaryan Jabbar Raouf,; Kawa Muhammad Faraj Qardaghi, (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Net income is one of the most important components of all commercial banks,) private or public (sector, which illustrates the financial stability of the bank, therefore the bank seeks to maintain and expand through the presence of sound management and success based on the components and principles of financial governance, the research aims to prove the relationship and effect of financial governance on the achievement of net income before tax. The research applied in the Kurdistan International Bank for Investment and Development (Private Shareholding), registered in the Iraqi Capital Markets Authority - the regular market, from the period 2014 to 2018, and after reviewing previous studies on financial governance Theoretical concepts and the research questions were written. We used the data were collected in the quarterly and annual reports of the Bank and Companies Directory of the Iraqi Stock Exchanges. While the correlation and regression coefficients for the period 2014 to 2018 were extracted. The study was based on a main hypothesis: Financial governance with its indicators (capital, investment, finance) affect the achievement of net income before tax at a level of 0.05. The results of the study showed that there were a significant statistical effect and relationship of financial governance indicators (investment, finance) in the net income before tax, and based on the results of the research a number of recommendations and suggestions were made